2004
DOI: 10.1210/me.2003-0145
|View full text |Cite
|
Sign up to set email alerts
|

Transient, Ligand-Dependent Arrest of the Androgen Receptor in Subnuclear Foci Alters Phosphorylation and Coactivator Interactions

Abstract: Here we report that mutations within the DNA-binding domain of AR, shown previously to inhibit nuclear export to the cytoplasm, cause an androgen-dependent defect in intranuclear trafficking of AR. Mutation of two conserved phenylalanines within the DNA recognition helix (F582, 583A) results in androgen-dependent arrest of AR in multiple subnuclear foci. A point mutation in one of the conserved phenylalanines (DeltaF582, F582Y) is known to cause androgen insensitivity syndrome (AIS). Both AIS mutants (DeltaF58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 64 publications
(75 reference statements)
5
50
0
Order By: Relevance
“…Moreover, we found that phosphorylation of the endogenous AR at Ser-81 in LNCaP cells was not increased until Ï·4 hr after androgen stimulation, indicating that it was not required for the expression of rapidly induced genes such as PLZF. This delay is consistent with data showing that Ser-81 is not phosphorylated until after DNA binding and transcription initiation and is progressively phosphorylated beyond 6 hr (12,24). Interestingly, the DHTstimulated expression of many other genes (including PSA) was delayed for several hours, but this delay with respect to PSA seems to reflect a requirement for new protein synthesis and is not clearly related to Ser-81 phosphorylation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, we found that phosphorylation of the endogenous AR at Ser-81 in LNCaP cells was not increased until Ï·4 hr after androgen stimulation, indicating that it was not required for the expression of rapidly induced genes such as PLZF. This delay is consistent with data showing that Ser-81 is not phosphorylated until after DNA binding and transcription initiation and is progressively phosphorylated beyond 6 hr (12,24). Interestingly, the DHTstimulated expression of many other genes (including PSA) was delayed for several hours, but this delay with respect to PSA seems to reflect a requirement for new protein synthesis and is not clearly related to Ser-81 phosphorylation.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies using an antibody against AR phospho-Ser-81 (pSer-81) have shown that phosphorylation at this site correlates with androgen-stimulated transcriptional activation and that this site is hypophosphorylated in mutants defective in DNA binding (15,24). In agreement with these results, AR Ser-81 in LNCaP PCa cells was not substantially phosphorylated in steroid hormone-depleted medium [RPMI medium 1640 with charcoal͞ dextran-stripped serum (CSS)] (Fig.…”
Section: Cdk1supporting
confidence: 70%
“…Although the knowledge of the functional significance of these sites is currently limited, it is well established that phosphorylation of serine 81 (Ser81) is hormone dependent (Gioeli et al, 2002;Black et al, 2004). Accordingly, we observed an increase in phosphorylation of Ser81 when hormone-depleted cells were stimulated with DHT ( Figure 6).…”
Section: Ser81 Phosphorylation Of the Armentioning
confidence: 62%
“…Although AR phosphorylation at residue Ser81 is a DHT-stimulated event (Gioeli et al, 2002;Black et al, 2004), the cellular function of this modification is not known. As the half-life of the AR is increased in response to androgens (Gregory et al, 2001), it is possible that phosphorylation of Ser81 is involved in this stabilization of the AR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation